(untitled) (The Pakistan Development Review, 1994)
Service providers and users are two key players in the efforts to regulate fertility in a society. Government policies and programmes ensure provision of services through increased coverage and adopting selective methods or a "cafeteria" approach. The objective for programme managers remains to bring adequate fertility impact without sacrificing pattern of use-continuation and overall efficiency of contraception. In contrast are the users, display another range of factors like preferences, motivation, ability to purchase and their stage of family building determining their participation in the fertility regulation behaviour. In this regard, the availability and accessibility to contraceptive methods referred to as the supply aspects of a system, outline the choice parameters for a user.